An assessment of ring seine fishery in Kerala through surplus production model - Balan, K; Sathianandan, T V (Indian Journal of Fisheries, 2011)
Outboard ring seine is one of the major gears operated in Kerala which contributes about 37% of the total landings in the State. Oil sardine (Sardinella longiceps) and Indian mackerel (Rastrelliger kanagurta) are the two species that account for about 84% of the ring seine catch. The ring seine fishery began in the State by mid eighties and grown into a major fishery over the years. An assessment of the ring seine fishery in the state through nonequilibrium surplus production model was made in this study by using time series data on catch and effort of ring seine in Kerala during 1986-2004. An index of relative biomass at and an index of net production rate mt were computed, apart from fishing mortality rates Ft, maximum sustainable yield (MSY), effort corresponding to MSY and biomass corresponding to MSY. Results revealed that the ring seine fishery in Kerala is close to the state of equilibrium. Behaviour of mt and Ft werealmost similar showing characteristics of fully developed fishery and the pattern of their difference mt-Ft indicated that the status of ring seine fishery in Kerala is close to the optimal level at present.